2002
DOI: 10.1590/s0102-05362002000400029
|View full text |Cite
|
Sign up to set email alerts
|

Capacidade de combinação entre linhas tetraplóides e diplóides de melancia

Abstract: Combining ability among tetraploid and diploid lines of watermelonCombining ability of three tetraploid (LT7-48.1, LT9-24.1 and LTCC-24) and four diploid lines of watermelon ('Crimson Sweet', 'Pérola', 'New Hampshire Midget' and 'Charleston Gray') was evaluated using a partial diallel scheme. A randomized block design, with three replications and seven plants in each field plot was used. Parents and F 1 's were evaluated regarding the number of days to the set of the first male and female flower, the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
1
4
0
2
Order By: Relevance
“…Sapovadiya et al (2014), who analyzed the combination ability of table watermelon, identified a significant additive effect in relation to AFW. Souza, Queiróz and Dias (2002) observed similar results for FL in diploid ant tetraploid table watermelon. Similarly, Bahari et al (2012), who studied production and fruit traits of watermelon did not observe any significance for NFP for GCA and SCA, the effects of which were observed in this study.…”
Section: Resultssupporting
confidence: 74%
“…Sapovadiya et al (2014), who analyzed the combination ability of table watermelon, identified a significant additive effect in relation to AFW. Souza, Queiróz and Dias (2002) observed similar results for FL in diploid ant tetraploid table watermelon. Similarly, Bahari et al (2012), who studied production and fruit traits of watermelon did not observe any significance for NFP for GCA and SCA, the effects of which were observed in this study.…”
Section: Resultssupporting
confidence: 74%
“…These results indicated the importance of both additive (σ 2 A) and non-additive genetic variance including dominance (σ 2 D) in the inheritance of many yield and its component traits. There is general agreement that GCA and associated heterotic effects are important determinates of parental choice during hybrid melon development (Ferreira et al 2002;Souza et al 2002). Moreover, heterosis, as a function of performance, is often related to degree of genetic relatedness and is ramatically influenced by growing environment.The estimated values of heterosis in broad sense (h 2 b%) were (97.14%, 95.24% and 94.0%) for taste band, flesh thickness and TSS%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Xiao et al (1996) demonstrated that the close relationship between genetic diversity of hybrids performance and heterosis in rice (Orzya sativa L. iaponica and Orzya sativa L. indica). There is general agreement that GCA and associated heterotic effects are important determinates of parental choice during hybrid melon development (Ferreira et al 2002;Souza et al 2002). Moreover, heterosis, as a function of performance, is often related to degree of genetic relatedness [i.e., genetic distance (GD)] and is dramatically influenced by growing environment.…”
Section: Introductionmentioning
confidence: 99%